2021
DOI: 10.1177/23333936211051702
|View full text |Cite
|
Sign up to set email alerts
|

Visitor Restrictions, Palliative Care, and Epistemic Agency: A Qualitative Study of Nurses’ Relational Practice During the Coronavirus Pandemic

Abstract: Efforts to curb spread of COVID-19 has led to restrictive visitor policies in healthcare, which disrupt social connection between patients and their families at end of life. We interviewed 17 Canadian nurses providing palliative care, to solicit their descriptions of, and responses to, ethical issues experienced as a result of COVID-19 related circumstances. Our analysis was inductive and scaffolded on notions of nurses’ moral agency, palliative care values, and our clinical practice in end-of-life care. Our f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 51 publications
(56 reference statements)
1
30
0
11
Order By: Relevance
“…Studies were conducted in Iran ( n = 4), China ( n = 2), Turkey ( n = 2), the United States ( n = 2), Canada ( n = 1), Jordan ( n = 1), Korea ( n = 1) and Sweden ( n = 1). In nine studies, the majority of participants were female; in two studies, all participants were female (Kwon & Choi, 2021 ; McMillan et al, 2021 ); in two studies, gender was not mentioned (Kelley et al, 2021 ; Silverman et al, 2021 ); and in one study, the majority of participants (60%) were male (Alloubani et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies were conducted in Iran ( n = 4), China ( n = 2), Turkey ( n = 2), the United States ( n = 2), Canada ( n = 1), Jordan ( n = 1), Korea ( n = 1) and Sweden ( n = 1). In nine studies, the majority of participants were female; in two studies, all participants were female (Kwon & Choi, 2021 ; McMillan et al, 2021 ); in two studies, gender was not mentioned (Kelley et al, 2021 ; Silverman et al, 2021 ); and in one study, the majority of participants (60%) were male (Alloubani et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of seven articles had the main objective related to topics on nurses' ethics during the COVID‐19 pandemic (Abbasinia et al, 2021 ; Alloubani et al, 2021 ; Jia et al, 2021 ; Karaca & Aydin Ozkan, 2021 ; Liu et al, 2021 ; McMillan et al, 2021 ; Rezaee et al, 2020 ; Stenlund & Strandberg, 2021 ), four articles (Kelley et al, 2021 ; Kwon & Choi, 2021 ; Moghaddam‐Tabrizi & Sodeify, 2021 ; Muz & Erdogan Yuce, 2021 ) had nurses' experiences in care of patients with COVID‐19 as main objective, one article (Silverman et al, 2021 ) was about moral distress in nurses caring for patients with COVID‐19, and the remaining article (Mohammadi et al, 2021 ) was conducted with nurses who were infected with COVID‐19. The participants' perceptions of ethical dilemmas are presented in the results of all 14 articles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a qualitative study, McMillan, et al, report nurses found the policies which separate people from families to be incongruent with nursing values and ethics. [27] Nurses are integral to an interdisciplinary team with social workers, recreation therapists, community liaisons, and administrators to connect residents with family or support persons using technology or by developing and implementing policies which meet both biomedical and humanistic needs.…”
Section: Nurses Need To Advocate On a Broader Arena Both Within And Beyond The Walls Of Ltc Nurses Contribute To Advocacy Bymentioning
confidence: 99%